Prevalence and antimicrobial resistance profiles of Vibrio spp. and Enterococcus spp. in retail shrimp in Northern California - Hirshfeld, Brady; Lavelle, Kurtis; Lee, Katie Yen; Atwill, Edward Robert; Kiang, David; Bolkenov, Bakytzhan; Gaa, Megan; Li, Zhirong; Yu, Alice; Li, Xunde; Yang, Xiang (Frontiers in Microbiology, 2023)
Shrimp is one of the most consumed seafood products globally. Antimicrobial drugs play an integral role in disease mitigation in aquaculture settings, but their prevalent use raises public health concerns on the emergence and spread of antimicrobial resistant microorganisms. Vibrio spp., as the most common causative agents of seafood-borne infections in humans, and Enterococcus spp., as an indicator organism, are focal bacteria of interest for the monitoring of antimicrobial resistance (AMR) in seafood. In this study, 400 samples of retail shrimp were collected from randomly selected grocery stores in the Greater Sacramento, California, area between September 2019 and June 2020. The prevalence of Vibrio spp. and Enterococcus spp. was 60.25% (241/400) and 89.75% (359/400), respectively. Subsamples of Vibrio (n=110) and Enterococcus (n=110) isolates were subjected to antimicrobial susceptibility testing (AST). Vibrio isolates had high phenotypic resistance to ampicillin (52/110, 47.27%) and cefoxitin (39/110, 35.45%). Enterococcus were most frequently resistant to lincomycin (106/110, 96.36%), quinupristin-dalfopristin (96/110, 87.27%), ciprofloxacin (93/110, 84.55%), linezolid (86/110, 78.18%), and erythromycin (58/110, 52.73%). For both Vibrio and Enterococcus, no significant associations were observed between multidrug resistance (MDR, resistance to ≥3 drug classes) in isolates from farm raised and wild caught shrimp (P > 0.05) and in isolates of domestic and imported origin (P > 0.05). Whole genome sequencing (WGS) of a subset of Vibrio isolates (n = 42) speciated isolates as primarily V. metschnikovii (24/42; 57.14%) and V. parahaemolyticus (12/42; 28.57%), and detected 27 unique antimicrobial resistance genes (ARGs) across these isolates, most commonly qnrVC6 (19.05%, 8/42), dfrA31 (11.90%, 5/42), dfrA6 (9.5%, 4/42), qnrVC1 (9.5%, 4/42). Additionally, WGS predicted phenotypic resistance in Vibrio isolates with an overall sensitivity of 11.54% and specificity of 96.05%. This study provides insights on the prevalence and distribution of AMR in Vibrio spp, and Enterococcus spp. from retail shrimp in California which are important for food safety and public health and exemplifies the value of surveillance in monitoring the spread of AMR and its genetic determinants.